Interaction, feedback and task research in second language learning methods and design - Mackey, Alison 1966- (Cambridge University Press, 2020)
"The role of interaction and corrective feedback is central to research in second language learning and teaching, and this volume is the first of its kind to explain and apply design methodologies and materials in an approachable way. Using examples from interaction, feedback and task studies, it presents clear and practical advice on how to carry out research in these areas, providing step-by step guides to design and methodological principles, suggestions for reading, short activities, memory aids and an A-Z glossary for easy reference. Its informative approach to study design, and in-depth discussions of implementing research methodology, make it accessible to novice and experienced researchers alike. Commonly used tools in these paradigms are explained, including stimulated recalls, surveys, eye-tracking, metanalysis and research synthesis. Open research areas and gaps in the literature are also discussed, providing a point-of-departure for researchers making their first foray into interaction, feedback and task-based teaching research. Alison Mackey is a leading international expert in input, interaction and feedback in L2 learning, and in L2 research methodology. She has published 16 books (one of which won the MLA's Mildenburger prize) and 100+ articles in these areas. At Georgetown University, where she is Professor of Linguistics, she has received both The President's Award for Distinguished Scholar Teachers and The Provost's Career Research Award"--
Keywords: Second language acquisition / Study and teaching; Language and languages / Study and teaching; Feedback (Psychology); Interaktion; Fremdsprachenunterricht; Rückmeldung; Aufgabenanalyse